Situationism and agency - Mele, A; Shepherd, J (Oxford Uehiro Centre for Practical Ethics, 2013)
Research in psychology indicates that situations powerfully impact human behavior. Often, it seems, features of situations drive our behavior even when we remain unaware of these features or their influence. One response to this research is pessimism about human agency: human agents have little conscious control over their own behavior, and little insight into why they do what they do. In this paper we review classic and more recent studies indicating “the power of the situation,” and argue for a more optimistic response. In our view, though psychological research indicates situational influence, it also indicates that knowledge about the impact of situations on behavior can boost agents’ power to counteract harmful situational effects.